Development of sample preparation methods for shotgun proteomic studies of white adipose tissue - Colnoe, Sayda (UiT Norges arktiske universitet, 2016)
Due to the lack of sunlight during the winter, people living in the arctic are unable to produce vitamin D3; hence deficiency of such vitamin is common in this part of the world. Given the geographic location of Norway, development of vitamin D deficiency is a common phenomenon. As vitamin D deficiency has become a public health issue, understanding the effects is vital for clinical implications. Studies have suggested that adipose tissues may be a direct target of vitamin D; especially the role of vitamin D in preventing the formation and development of adipocyte and of which has become of great interest to this study. Therefore, in order to investigate the potential role of vitamin D deficiency in relation to adipose tissue, Liquid chromatography-tandem mass spectrometry (LC-MS/MS) based shotgun analysis of adipose tissue proteome seems appropriate for this study. This research seeks to develop a method that will quantify and identify white adipose tissue proteins. Hence, the appropriate method identify will be used in a vitamin D placebo controlled trial. To address this, the following seven different detergents efficiency methods to extract hydrophobic proteins were compared in triplicates for each sample as follows: PPS Silent (Sodium 3-(4-(1,1-bis (hexyloxy) ethyl) pyridinium-1-yl)- propane-1-sulfonate), ProteaseMAX (Sodium 3-((1-(furan-2-yl) undecyloxy) carbonylamino) propane-1-sulfonate), RapiGest (Sodium 3-[(2-methyl-2-undecyl- 1,3-dioxolan-4-yl) methoxy]- 1-propanesulfonate), Urea-Chaps (Urea-3-[(3-Cholamidopropyl) dimethylammonio]-1-propanesulfonate), SDS (Sodium dodecyl sulfate), SDC (Sodium deoxycholate) and SL (Sodium laurate). Two protein precipitation methods (acetone and ethanol) were compared using SDS and CHAPS-Urea samples as the basis for analysis after the acetone and ethanol precipitation (AP and EtOHP) procedures. Filter-aided sample preparation (FASP) was also carried out on the two samples mentioned above using a 30 kDa filter. The results showed that PPS Silent, ProteaseMAX and ...